The NF-kB and Collagen Type 1 Expression in Dental Pulp after Treated Calcium Hydroxide Combined with Propolis - Pribadi, Nirawati; Budiarti, Dwita; Kurniawan, Hendy Jaya; Widjiastuti, Ira (European Journal of Dentistry, 2021)
Objective To analyze the expression of nuclear factor kappa B (NF-kB) and collagen type 1 on dental pulp after a treated combination of calcium hydroxide and propolis.Materials and Methods The first maxillary molars of 30 rats were mechanically perforated. Teeth were divided into three groups of 10 for two separate extraction time frames, giving a total of 60 rats. The control groups were treated with Cention, the second treatment groups were treated with calcium hydroxide, and the third treatment groups were treated with a combination of calcium hydroxide and propolis. Final restoration was done with Cention. The teeth were extracted on days 7 and 14, and the expression of NF-kB and collagen type I was analyzed using immunohistochemistry.Results There is lowest NF-kB expression and highest collagen type 1 expression on dental pulp after treated with a combination of calcium hydroxide and propolis on days 7 and 14 (p < 0.05).Conclusion The combination of calcium hydroxide and propolis inhibits pulp inflammation and stimulates regeneration through decreasing the NF-kB expression and increasing collagen type 1.
Keywords: calcium hydroxide; propolis; collagen type 1; NF-kB